Effectiveness of deep Brain Stimulation on early onset Dystonia: A Case Report - Ayse Unal; Ali Yalman; Filiz Altug; Uğur Cavlak (Open Journal of Parkinson's Disease and Treatment - Peertechz Publications, 2017)
Dystonia is defined as a movement disorder characterized by involuntary muscular contractions that generate twisting and repetitive movements and/or abnormal postures [1]. The traditional clinical categorization of the dystonias based on age at onset, distribution of symptoms (focal, segmental, multifocal, generalized), and site of onset remains important and overlaps with the more recently employed genetic classification. Early-onset primary dystonia is a condition characterized by progressive problems with movement, typically beginning in childhood [2]. Early-onset dystonia often starts in a limb, tends to generalize and frequently has a genetic origin; whereas adult-onset dystonia usually spares the lower extremities, frequently involves cervical or cranial muscles with a tendency to remain focal, and appears sporadic in most cases [3].